1)(x-1 15/16)+7 3/16=8 1/16+4 9/16
(x-1 15/16)+7 3/16=12 10/16
(x-1 15/16)=12 10/16-7 3/16
(х- 1 15/16)=5 7/16
х=5 7/16+1 15/16
х=6 22/16
х=7 6/16
х=7 3/8
ответ. х= 7 3/8
2)15 3/28-(4 11/28+у)=5 19/28
4 11/28+у=15 3/28-5 19/28
4 11/28+у=14 31/28-5 19/28
4 11/28+у=9 12/28
у=9 12/28-4 11/28
у=5 1/28
1)(x-1 15/16)+7 3/16=8 1/16+4 9/16
(x-1 15/16)+7 3/16=12 10/16
(x-1 15/16)=12 10/16-7 3/16
(х- 1 15/16)=5 7/16
х=5 7/16+1 15/16
х=6 22/16
х=7 6/16
х=7 3/8
ответ. х= 7 3/8
2)15 3/28-(4 11/28+у)=5 19/28
4 11/28+у=15 3/28-5 19/28
4 11/28+у=14 31/28-5 19/28
4 11/28+у=9 12/28
у=9 12/28-4 11/28
у=5 1/28